The Development of Based Evaluation Instruments Wordwall for Science Courses of Junior High School Class VII - Auliya, Anisa; Suhirman, Suhirman; Latipah, Nurlia (Universitas Islam Negeri Antasari Banjarmasin, South Kalimantan, Indonesia, 2021)
The evaluation instrument or evaluation tool is a tool that meets academic requirements, so that it can be used as a measuring tool or data collection about a variable. Based on the results of the analysis of the need for evaluation instruments used by educators in learning, the teacher still uses paper and google forms for evaluation. This research aims to develop a Wordwall-based evaluation instrument and to determine student responses to wordwall-based evaluation instruments. The type of research used is Research and Development (R&D). The development model used is the Borg and Gall model adapted by Sugiyono with 8 stages consisting of needs analysis, data collection, product design, design validation, design revision, small-scale testing, product revision and user testing. The results of the development of a wordwall-based evaluation instrument for class VII junior high school science subjects obtained values from the validation of material, media and language experts of 80%, 98.5% and 96.65% with very feasible categories. Whereas for the results of the trial use, the average result of the student's questionnaire response was 87.9% with the very interesting instrument category.